Alternative medicine in Islam: concepts and acts - ElSayed, Khalid Abdelhay; Othman Talib; Fariza Md. Sham (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2013)
This paper deals with some concepts and Islamic legal acts that are closely linked to the field of alternative medicine, where they are aimed at elaborating what both therapist and patient need to know before treatment, so that, the required results of therapy and Dakwah can come true. They will only come true if important concepts in the field of the principles of faith needed by both therapist and patient are complied with. Patient should also be awakened to the concept of Ibtila in which a believer is tested by Allah and its advantages and wisdom. The paper also deals with the concept of patience and some related aspects. A patient must also be awakened to a number of Islamic legal acts that are closely linked to the subject of alternative medicine, such as what does Islam say about treating with medicine and treating with the prohibited, while the Islamic acts concerning the case where a foreign woman is treated by a man and vice versa and the case where a therapist is paid for his service are also explained. The Islamic legal acts concerning the issue where a patient can be insured against loss of health if he is mistakenly treated are also elaborated. The paper finally deals with the quarantine-like system introduced by Islam during which patients suffering from a contagious disease are placed in enforced isolation. The two writers concluded that both therapist and patient should know the advantages and wisdom of Ibtila and the virtue of patience. Both must also be aware of the Islamic legal acts concerning the Islamic alternative medicine. For example, can a therapist be paid? Can one treat himself with medicine? And many more questions that are discussed at length in the books of jurisprudence.